Malaysia Tourists' Visit and Revisit Intentions Post COVID Pandemic - Chaichi, Kamelia *; Leong, Mei Kei *; Trupp, Alexander *; Nezakati, Hossein * (2022)
Prior to the pandemic, Malaysia ranked 22nd tourism destination in the world. However, the number of tourist arrivals in 2020, decreased by -83.4% compared to 2019. Malaysia has the potential to be one of the top destinations for travellers due to different cultural attractions, heritage, and natural attractions. Considering the importance of international tourism to Malaysia’s economic growth, and the image of the country current research applies a mixed method approach to explore the reasons for international tourists' intention to visit and revisit Malaysia and provide practical implications for the further development of international travel in Malaysia for the Covid-19 recovery.